Fungal Infections in Major Burns - 2 Years Overview - Andra Luana LAZARESCU; Andreea GROSU-BULARDA; Mihaela-Cristina ANDREI; Sabina GRAMA; Adrian FRUNZA; Dan Aurel IONESCU; Serban ARGHIR POPESCU; Tiberiu Paul NEAGU; Ioan LASCAR (Modern Medicine, 2020)
Infections are the most severe and the most frequent complication in major burns requiring adequate diagnosis and treatment. Extensive burned areas, impaired immune system and antibiotic therapy contribute to the development of opportunistic fungal infections. An important aspect is the increased level of antimicrobial resistance in our country. We present a two years study on the burn patients hospitalized in our institution. A total of 355 burned patients were hospitalized during this period, 210 (59%) of them being addmited in Critical Care Burn Unit. We noted the main infectious complications and established a dinamic microbian mapping during patient hospitalization. Fungal infections were noted. We performed microbiological screening: testing at admission and once a week or in case of clinical signs from all potential sites. For the clinical therapy of mycoses, it is mandatory to know whether a fungal colonization or a fungal infection is involved. Unfortunately, often in severe burned patients, clinical presentation is unspecific and sensitivity of diagnostic results may be unreliable. Invasive fungal infections due to Candida species and Aspergillus species are important emerging causes of morbidity and mortality. The systemic use of antifungal agents is conducted depending on the general condition of the burn patient, the fungal species involved and the confirmation of fungemia. In conclusion, specific treatment of infectious complications has to be conducted according to the characteristics of the patients in order to reduce morbidity and mortality and avoid the development of antimicrobial resistance.